Benefits of chronic blood transfusion in hemoglobin E/β thalassemia with pulmonary arterial hypertension - Nonlawan Chueamuangphan (2018)
Objective: The aim of the research reported here was to compare pulmonary artery systolic pressure (PASP) and 6-minute walk distance after 1 year of follow-up in hemoglobin E/β thalassemia (E/β-Thal) with pulmonary arterial hypertension (PAH) patients who received chronic blood transfusions versus those who received occasional transfusions. Methods: A nonrandomized clinical trial was conducted at the Hematological Outpatient Clinic of Chiang Rai Hospital, Thailand. All adult cases of E/β-Thal with PAH (defined as PASP >35 mmHg by Doppler echocardiography) were evaluated and followed for the next 12 months. The patients were classified into two groups by patient preference. Group 1 patients received chronic blood transfusions - one to two units of leukocyte-poor packed red cells every 2-4 weeks - over 1 year to maintain pre-transfusion hemoglobin levels of ≥7.0 g/dL. Group 2 patients received occasional transfusions over the course of 1 year, with more than 4 weeks between transfusions. All patients were treated with iron chelation when serum ferritin levels were > 1,000 μg/dL. PASP and the 6-minute walk distance were evaluated at baseline and at 6 and 12 months. Propensity score adjustment was used to control for confounding by indication and contraindication. Multivariable regression analysis was used to evaluate the effects of chronic blood transfusion. Results: There were 16 (53.3%) patients in Group 1 and 14 (46.7%) in Group 2. At 12 months, patients in Group 1 had a greater reduction in PASP than those in Group 1 (adjusted mean difference, -16.83; 95% confidence interval, -26.35 to -7.32; P=0.001). The 6-minute walk distance at 12 months in Group 1 patients was greater than that in Group 2 patients (adjusted mean difference, 46.55; 95% confidence interval, 18.08 to 75.02; P=0.001). Conclusion: This study found evidence that chronic blood transfusions may have beneficial effects in PAH in thalassemia patients over 1 year. © 2014 Chueamuangphan et al.